Coupled piezoelectric fans with two degree of freedom motion for the application of flapping wing micro aerial vehicles - Chung, H. C.; Lal Kummari, K.; Croucher, S. J.; Lawson, Nicholas J.; Guo, Shijun J.; Huang, Zhaorong (Elsevier Science B.V., Amsterdam., 2008)
Piezoelectric fans consisting of a piezoelectric layer and an elastic metal layer were prepared by epoxy bonding and a coupled flexible wing was formed by a pair of carbon fibre reinforced plastic wing spars and polymer skin attached to two piezoelectric fans. Two sinusoidal voltages with phase differences were then used to drive the coupled piezoelectric fans. High speed digital cameras were used to characterize the two degree of freedom (DOF) motion of the wing and these results were compared to finite element model of the wing and the coupled piezoelectric fans. It has been observed that the phase delay between the driving voltages applied to the coupled piezoelectric fans plays an important role in the control of the flapping and twisting motions of the wing and this set-up has the potential for application to the control of flapping wings for micro aerial vehicles. (c) 2008 Elsevier B.V. All rights reserved.